2021
DOI: 10.1016/j.xjon.2021.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of consistent guideline-based tricuspid management in patients undergoing degenerative mitral regurgitation correction

Abstract: Objectives: Despite coherent guidelines, management of functional tricuspid regurgitation (FTR) consequences on outcome in the context of degenerative mitral regurgitation (DMR) remains controversial due to lacking series of large magnitude with rigorous application of tricuspid guidelines and strict long-term echocardiographic follow-up. Thus, we aimed at gathering such a cohort to examine outcomes of patients undergoing DMR surgery following tricuspid surgery guidelines.Methods: All consecutive patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…In the authors’ study population, 39% of the TA group had preoperative atrial fibrillation (AF) compared with 23% in the no-TA group. 2 Preoperative AF was associated with TR progression in the group with no TA, although 10% of the patients in the no-TA group underwent surgical ablation versus 23% in the TA group. Kim and colleagues 7 found that the omission of AF ablation was associated with deterioration of TR in patients with preoperative mild TR following tricuspid repair during rheumatic mitral surgery.…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…In the authors’ study population, 39% of the TA group had preoperative atrial fibrillation (AF) compared with 23% in the no-TA group. 2 Preoperative AF was associated with TR progression in the group with no TA, although 10% of the patients in the no-TA group underwent surgical ablation versus 23% in the TA group. Kim and colleagues 7 found that the omission of AF ablation was associated with deterioration of TR in patients with preoperative mild TR following tricuspid repair during rheumatic mitral surgery.…”
mentioning
confidence: 87%
“…Perhaps the most important finding from the article by Dreyfus and colleagues 2 is the reaffirmation of the inadequacy of our understanding of the complex topic of FTR. Dreyfus acknowledged that there is uncertainty about the factors that contribute to annular dilatation in patients with FTR, and clearly factors other than the severity of TR and the annular size influence TR progression and clinical outcomes.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Annular pathology seems such a correctable target for surgical intervention, particularly given the association between tricuspid annular diameter (>40 mm) and late right heart failure ( 21 ). However, recent studies of patients undergoing guideline—directed repair of functional TR (annular diameter > 40 mm independent of TR severity) at the time of mitral surgery demonstrate no differences in survival and the incidence of “late TR” is low in patients with unrepaired mild TR ( 22 ). While Gammie et al ( 23 ) recently demonstrated a lower incidence of progression to TR in patients who underwent tricuspid annuloplasty at the time of mitral valve repair, preliminary data do not address the role of recurrent mitral regurgitation on the subsequent evolution of tricuspid insufficiency.…”
Section: Is It the Tricuspid Valve… Are We Measuring The Wrong Thing?mentioning
confidence: 99%